Examining Building Engineering Education Students' Reading and Listening Skills Using the EF Standard English Test - Rahayu, Diana; Iswardhany, Rieske (Universitas Pendidikan Indonesia (UPI), 2025)
In facing the era of globalization where the demand for foreign language proficiency is increasing, learning foreign languages, especially English, becomes very important. Because of this, Universitas Pendidikan Indonesia (UPI) requires students who will register for the graduation thesis defense to attach an English proficiency certificate. Considering that the main focus of the curriculum in the Building Engineering Education program is not English, it is necessary to analyze their English proficiency level before taking the English course. The method used is an online test through the EF SET website, the results of which will then be converted into CEFR categories consisting of seven levels of English proficiency. Based on the analysis results, the English proficiency levels of class A and class B students in terms of listening and reading comprehension are assessed to be in the upper beginner category. In the reading comprehension aspect, class A students fall into the intermediate category with a percentage of 30.8%, while the beginner and elementary categories each receive less than 30%, with the remainder in the upper intermediate and advanced categories at 5%, and less than 3% at the proficient level. Meanwhile, for class B, 30% are at the beginner level, followed by the largest group at the elementary level (25%), then intermediate (16.7%), upper intermediate (11%), and advanced and proficient levels at less than 10%. In the listening comprehension aspect, both class A and class B are at the beginner level with percentages of 48% and 52%, respectively.